Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1161/01.cir.77.3.654
|View full text |Cite
|
Sign up to set email alerts
|

Time domain echo pattern evaluations from normal and atherosclerotic arterial walls: a study in vitro.

Abstract: The aim of this study in vitro of human fresh specimens was to quantitatively evaluate the contribution of the aqueous phase-intima interface (the first 400 msec of the reflected signal) in normal and atherosclerotic arterial walls. Seventy-five samples were studied, 15 normal, 15 fatty, 15 fibrofatty, 15 fibrous, and 15 calcific. A broadband transducer (4 to 14 MHz) was used. The aqueous phase-intima reflection (expressed in dB, mean + SD) was lowest in the fatty plaques (-35.3 + 2.5), differing in a highly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
(24 reference statements)
1
26
0
Order By: Relevance
“…This 'double peak' signal is very similar to the 'double-line pattern' observed on the typical B-mode image of a longitudinally scanned normal artery wall [22][23][24] and has been related to the distinct acoustic interfaces between intima, media and adventitia. Although the origin of these ultrasonographic layers re mains controversial, it has been suggested that the first high-amplitude signal reflects the lumen-intima interface, the hypoechogenic zone part of the media, and the second high-amplitude signal the media-adventitia interface [7].…”
Section: Discussionsupporting
confidence: 70%
“…This 'double peak' signal is very similar to the 'double-line pattern' observed on the typical B-mode image of a longitudinally scanned normal artery wall [22][23][24] and has been related to the distinct acoustic interfaces between intima, media and adventitia. Although the origin of these ultrasonographic layers re mains controversial, it has been suggested that the first high-amplitude signal reflects the lumen-intima interface, the hypoechogenic zone part of the media, and the second high-amplitude signal the media-adventitia interface [7].…”
Section: Discussionsupporting
confidence: 70%
“…[9][10][11][12][13][14][15] We performed ultrasonographic examinations of the carotid arteries and assessed the acoustic properties of atherosclerotic plaques by means of a suitably modified echographic apparatus allowing direct access to the radiofrequency signal in 15 patients who subsequently underwent endarterectomy. The ultrasonic findings were correlated with the histological analysis, independently performed on the arterial samples.…”
mentioning
confidence: 99%
“…In studies of the myocardium, calibrated myocardial IB values were significantly correlated with the relative volume of interstitial fibrosis (Picano, 1990 et al;Naito et al, 1996). In preliminary studies in vitro, IB values reflected the structural and biochemical composition of atherosclerotic lesion and could differentiate fibrofatty, fatty and calcification of arterial walls (Barziliai et al, 1987;Urbani et al, 1993;Picano et al, 1988). It was also reported that anisotropy of the direction and backscatter power is related to plaque type (De Kroon et al, 1991).…”
Section: Introductionmentioning
confidence: 95%